2014
DOI: 10.1002/ppap.201400013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Modification of Copper Nanoparticles on their Antibacterial Properties

Abstract: Surface modification of copper nanoparticles (CuNPs) was performed in a radiofrequency plasma reactor using acrylic acid, acrylonitrile, and methyl methacrylate monomers. Treated and untreated CuNPs were analyzed by thermogravimetrical analysis, X-ray diffraction (XRD), transmission electronic microscopy, energy dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy. The oxidation of CuNPs was assessed by XRD as a function of the plasma treatment. The antibacterial properties of plasma trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…The BCs containing nanoCu or both nanometals have not been investigated yet. Some investigations of nanoCu in polymer matrices and its bactericidal properties are consistent with the present results (Table 2) [80,81,82].…”
Section: Discussionsupporting
confidence: 92%
“…The BCs containing nanoCu or both nanometals have not been investigated yet. Some investigations of nanoCu in polymer matrices and its bactericidal properties are consistent with the present results (Table 2) [80,81,82].…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the films had a bactericidal effect against Grampositive methicillin-resistant Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa [120]. Similarly, other work has shown that the use of acrylic acid coatings on Cu NPs does not affect their biocidal properties [121]. This fact is relevant, because on the one hand the surface treatment of NPs does not inhibit their biocidal properties and, on the other hand, they have the capacity to have good interfacial adhesion with the polymeric matrices, thus generating multifunctional properties of PNCs.…”
Section: Treatment Of Nps Prior To Pncs Processingmentioning
confidence: 72%
“…In addition to the use of CAP as implant coatings, CAP have been used to enhance the antibacterial properties of CuO‐NPs by enhancing their biocompatibility as well as antibacterial activity by achieving thin layers of various polymers on their surface. This prevents the oxidation of metallic NP, and allows the diffusion of metal ions that will act as antimicrobials primarily with the additional dispersing effect of the plasma‐polymerized surface modifications 142,143. Therefore, CAP treatment is ascribed to ease the preparation of antibacterial coatings and enhancing the impact that can be employed as preventive strategies for the bacterial infections.…”
Section: Nanomaterial‐integrated Diagnosis Prevention and Therapy Omentioning
confidence: 99%